A study the level of understanding on corruption among muamalat’s student at UiTM Puncak Alam / Hazira Tun Najihah Hj Mohd Akahsah - Hj Mohd Akahsah, Hazira Tun Najihah (2019)
This study examine the level of understanding on corruption among Muamalat’s Student At Uitm Puncak. The understanding needs to be understood because more and more university students are willing to give in to corruption, this is based on an increase in the percentage of university students who are willing to accept and give bribes based on a study by the Malaysian Anti-Corruption Commission (MACC). A survey data by the respondents of students using Statistical Package for Social Sciences (SPSS). Results reveal a understanding of corruption at a satisfactory level. To conclude, the purpose of this study is to look at the extent to which students understand corruption..